2018
DOI: 10.1038/s41375-018-0184-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition to B-cell acute lymphoblastic leukemia at 14q11.2 is mediated by a CEBPE promoter polymorphism

Abstract: Acute lymphoblastic leukaemia (ALL) is the most common paediatric malignancy. Genome-wide association studies have shown variation at 14q11.2 influences ALL risk. We sought to decipher causal variant(s) at 14q11.2 and the mechanism of tumorigenesis. We show rs2239630 G>A resides in the promoter of the CCAT enhancer-binding protein epsilon (CEBPE) gene. The rs2239630-A risk allele is associated with increased promotor activity and CEBPE expression. Depletion of CEBPE in ALL cells reduces cell growth, correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…For example, rs2239630G/A is present in the promoter of the CCAT enhancer-binding protein epsilon (CEBPE) gene. The rs2239630A allele can enhance promoter activity and CEBPE expression and is associated with the risk of acute lymphoblastic leukemia [21]. The Matrix metalloproteinase (MMP-9) gene promoter polymorphism − 1562C/T regulates its transcriptional activity and affects the course of thyroid carcinoma [22].…”
Section: Discussionmentioning
confidence: 99%
“…For example, rs2239630G/A is present in the promoter of the CCAT enhancer-binding protein epsilon (CEBPE) gene. The rs2239630A allele can enhance promoter activity and CEBPE expression and is associated with the risk of acute lymphoblastic leukemia [21]. The Matrix metalloproteinase (MMP-9) gene promoter polymorphism − 1562C/T regulates its transcriptional activity and affects the course of thyroid carcinoma [22].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, double homeobox A pseudogene 10, located in chr14q11.2, promotes an aggressive phenotype by binding lysine-specific histone demethylase 1 and repressing large tumor suppressor kinase 2 and Ras-related glycolysis inhibitor and calcium channel regulator expression levels in NSCLC (17). Furthermore, previous studies have revealed that chr14q11.2 may participate in cancer development (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting example of SNPs, associated with susceptibility to cALL and affecting metabolic genes indirectly, is an SNP located in the promoter of the transcription factor CEBPE which activates the promoter leading to upregulation of CEBPE levels. The transcription factor, in turn, upregulates the expression of ETC and energy production genes 50 …”
Section: Cell Metabolism In Callmentioning
confidence: 99%